Effective Dose of Rhizoma Coptidis Extract Granules for Type 2 Diabetes Treatment: A Hospital-Based Retrospective Cohort Study - Huang, Yueh-Hsiang; Liu, Geng-Hao; Hsu, Tzu-Yang; Yang, Lan-Yan; Lee, Ming-Chung; Huang, Chun-Teng; Wu, Yi-Hong (Frontiers in Pharmacology, 2021)
Rhizoma Coptidis is a popular phytomedicine for the treatment of type 2 diabetes in Asia, but its effective dose for diabetes treatment remains confused because of diverse origins. This study aimed to investigate the dose-response effects of Rhizoma Coptidis extract granules (RCEG), produced with standardized quality control, on hypoglycemic effects in patients with type 2 diabetes. We conducted a retrospective analysis of Chang Gung Research Database from January 01, 2008 to November 30, 2017. Outpatients visiting traditional Chinese medicine clinics and receiving RCEG for type 2 diabetes treatment were included. Plasma glucose, lipid, and other parameters were analyzed from 93 patients with a total of 737 visits within 60 weeks. Scatter plots with the LOESS analysis were used to explore the association between RCEG dose and hypoglycemic effect. The minimal effective dose was chosen to divide the study population into the high-dose and low-dose RCEG groups. Non-parametric tests were used for between-group and within-group comparisons. The multivariate nonlinear mixed-effects model was applied to access the effect of treatment length and groups simultaneously on the change of HbA1c and fasting plasma glucose. The “arule” package in R was used to present the network diagram of RCEG and other co-prescriptions. We first discovered a significant relationship between RCEG dose and HbA1c reduction when the dose reached 0.08 g/kg/day or higher. We thus defined 0.08 g/kg/day of RCEG as the minimum effective dose, and a threshold to separate patients into the high-dose (≥0.08 g/kg/d) and low-dose (<0.08 g/kg/d) RCEG groups. In the high-dose RCEG group, a significant decrease in total cholesterol and a trend toward triglyceride reduction were also noted. Patients more effectively responded to RCEG treatment if they had a higher initial HbA1c level, higher heart rates, better liver function tests, and better tolerance to the higher dose and treatment duration of RCEG. In addition, digestive/tonic/dampness draining formulas and blood regulation recipes were two of the most frequent co-prescriptions with RCEG. This study concluded that RCEG at a dose exceeding 0.08 g/kg/d had beneficial effects on glycemic and lipid control, without showing nephro- or hepatotoxicity, in patients with type 2 diabetes.